Study on recycle of granulated blast-furnace slag as an adsorbent for ammonium remediation in wastewater - Trinh Minh Viet; Nguyen Tuan Minh; Nguyen Thi Phuong Thao; Phung Linh Phuong; Trinh Van Tuyen (Vietnam Journal of Science and Technology, 2023)
Blast-furnace slag (BFS) is enormously generated each year and has been considered as hazardous solid waste which is posing a significant pressure on waste treatment in terms of storage and transportation. This study aims to recycle BFS as a material for ammonium adsorption from an aqueous solution. Natural-state BFS and acidic-modified by using HNO3 at various concentration of 0.5M, 1M, and 3M (A-BFS1, A-BFS2, and A-BFS3) was examined. The surface characteristics of the materials were examined by BET analysis and Scanning Electron Microscope. The adsorption of ammonium on the BFS materials was conducted in batch mode at various conditions of contact time, pH level, adsorbent dosage, and initial concentration of ammonium. The results indicated that the HNO3 modification exhibited pore creations and surface enhancement as the A-BFS3 has 25.7 times larger surface area and 10.3 times pore size improvement. The A-BFS3 showed good ammonium adsorption capacity compared to other materials, which is 1.81 mg/g at the optimum conditions of pH 6, contact time of 120 minutes, and dosage of 0.5 g in 50 mL of 20 mg/L ammonium solution. Langmuir and Freundlich adsorption isotherm models of the A-BFS3 material showed a relatively good correlation with R2 values of 0.999 and 0.9625, respectively.